Cantwell, Theresa Squires. Black and white photograph of two girls and a boy in a field from Theresa Squires Cantwell's personal photograph collection. - Barrett, Terra (1950)
Left to right: Patrick Squires, Eileen Squires, Theresa Squires on Squires property. Three siblings. Theresa was born in 1944.